ANALYSIS OF THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, JOB DESIGN AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENTION VARIABLE - Helmaini Sinaga; Darmilisani; Kholilul Kholik (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of transformational leadership, job design, and work experience on employee performance with work discipline as an intervening variable at the Regional Office of the Directorate General of Corrections, North Sumatra. The problem in this study is the employee performance that has not been optimal, which is influenced by several factors such as transformational leadership, job design, work experience, and work discipline. This study used a quantitative approach with an associative research type. The population in this study consisted of all employees at the Regional Office of the Directorate General of Corrections, North Sumatra. The sampling technique used was saturated sampling, in which the entire population was used as the research sample. Data were collected through questionnaires. The data analysis method used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS software. The results showed that job design had a positive and significant effect on work discipline and employee performance. Work discipline also had a positive and significant effect on employee performance. Transformational leadership had a positive and significant effect on work discipline, but did not have a significant effect on employee performance. Work experience had a positive and significant effect on work discipline, but did not have a significant effect on employee performance. In addition, work discipline was able to mediate the influence of job design, transformational leadership, and work experience on employee performance. The conclusion of this study indicates that work discipline plays an important role in improving employee performance. Therefore, the institution needs to improve job design, the implementation of transformational leadership, and the development of employees’ work experience in order to create better work discipline so that employee performance can improve optimally. This study aims to analyze the influence of transformational leadership, job design, and work experience on employee performance with work discipline as an intervening variable at the Regional Office of the Directorate General of Corrections, North Sumatra. The problem in this study is the employee performance that has not been optimal, which is influenced by several factors such as transformational leadership, job design, work experience, and work discipline. This study used a quantitative approach with an associative research type. The population in this study consisted of all employees at the Regional Office of the Directorate General of Corrections, North Sumatra. The sampling technique used was saturated sampling, in which the entire population was used as the research sample. Data were collected through questionnaires. The data analysis method used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS software. The results showed that job design had a positive and significant effect on work discipline and employee performance. Work discipline also had a positive and significant effect on employee performance. Transformational leadership had a positive and significant effect on work discipline, but did not have a significant effect on employee performance. Work experience had a positive and significant effect on work discipline, but did not have a significant effect on employee performance. In addition, work discipline was able to mediate the influence of job design, transformational leadership, and work experience on employee performance. The conclusion of this study indicates that work discipline plays an important role in improving employee performance. Therefore, the institution needs to improve job design, the implementation of transformational leadership, and the development of employees’ work experience in order to create better work discipline so that employee performance can improve optimally.